Effect of TiO2 nanostructure morphology on the performance of a photoelectrochemical cell of ITO/TiO2/electrolyte/platinum - Rahman M.Y.A.; Umar A.A.; Roza L.; Salleh M.M. (2023)
The morphology of photovoltaic material is able to influence of the performance of photoelectrochemical cell. Polyvinylpyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB), and hexamethylenetetramine (HMT) surfactant were used to modify the morphology nanostructure of TiO2 films by a simple technique, namely, liquid phase deposition during their growth process. It was found that the untreated surfactant TiO2 film produces the morphology with the mixture nanosphere and nanoflower. The film treated with PVP, CTAB, and HMT produce the nanostructure shape of nanoflower, nanowire, and nanorod, respectively. These TiO2 samples were utilized as photovoltaic materials in a photoelectrochemical cell of ITO/TiO 2/electrolyte/platinum. It was found that the photovoltaic parameters such as short-circuit current density (Jsc), open-circuit voltage (Voc) and fill factor are influenced by the morphology in terms of shape and particle size of the TiO2 nanostructure. The cell utilizing the TiO2 nanowire treated with PVP possesses the highest Jsc and Voc of 0.100 mAcm -2 and 0.44 V. The length of the TiO2 nanowire is 62 nm, while the cell with the untreated surfactant TiO2 sample demonstrates the lowest performance. It was also found that the Jsc and Voc increase with the decrease in the length of the TiO2 nanostructures. The smallest length of TiO2 possesses the best interfacial contact at TiO2/electrolyte containing iodide/triiodide redox couple. Thus, the redox reaction is optimized at this interface. Springer-Verlag 2012.